1994
DOI: 10.1200/jco.1994.12.3.569
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of combined 2-chlorodeoxyadenosine and chlorambucil in chronic lymphoid leukemia and low-grade lymphoma.

Abstract: These observations suggest the possibility of combining two cycles of continuous intravenously administered 2-CdA (2 mg/m2/d for 7 days) with standard doses of oral chlorambucil to test the efficacy of the combination regimen in phase II trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 29 publications
0
17
1
Order By: Relevance
“…In contrast to other studies using cladribine in association with either chlorambucil or mitoxantrone (Tefferi et al, 1994;Saven et al, 1996), the infection rate of our CCP combination was acceptable. This may indeed be attributable to selection bias as over 50% of the patients were previously untreated and could have better tolerated the treatment.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…In contrast to other studies using cladribine in association with either chlorambucil or mitoxantrone (Tefferi et al, 1994;Saven et al, 1996), the infection rate of our CCP combination was acceptable. This may indeed be attributable to selection bias as over 50% of the patients were previously untreated and could have better tolerated the treatment.…”
Section: Discussioncontrasting
confidence: 46%
“…The same range of complications has been shown with cladribine given in combination with either chlorambucil or mitoxantrone to patients with indolent lymphoid malignancies (Tefferi et al, 1994;Saven et al, 1996). Early enthusiasm for the association of cladribine with other active cytotoxic agents may thus have been hampered by such adverse experiences.…”
mentioning
confidence: 87%
“…Several Phase I and II trials have piloted combinations of 2-CdA with mitoxantrone, [40][41][42] cyclophosphamide, 43,44 and chlorambucil. 45 However, in those initial trials, response rates from 28.5% to 90% (CR rate, 7.1-44%) appear similar to single-agent trials, and toxicities may be increased.…”
Section: Discussionmentioning
confidence: 99%
“…59 The authors have shown that sequential therapy in previously untreated CLL patients is safe and can improve the quality of response in a large patient population compared to the therapy with FAMP alone. A similar study has been recently performed by Tefferi et al 88 They started the treatment with six cycles of intravenous CY (1 g/m 2 ) plus prednisone (100 mg/m 2 /day for 5 days) followed by 2 to 6 cycles of 2-CdA (5 mg/m 2 /day for 5 days). The OR and CR rates were 90% and 33%, respectively.…”
Section: Nucleoside Analogues Combined With Alkylatorsmentioning
confidence: 99%
“…A synergistic antitumour effect of chlorambucil was seen in CLL cells in vitro with DCF and 2-CdA. 88,89 The early clinical trials investigating the combination of chlorambucil with 2-CdA or FAMP in heavily pre-treated as well as previously untreated patients with CLL provided evidence that marrow suppression and infections were dose-limiting factors and that the doses of NA had to be lower in combination than in monotherapy. 89,90 …”
Section: Leukemiamentioning
confidence: 99%